An Information Systems Study on the U.P. Consumer's Cooperative, Incorporated - Alban, Margie C. (College of Engineering, 1997)
The first U.P. Cooperative was established before the war at the old U.P. site in Padre Faura, Manila. In 1946, a move to organize the cooperative was started. Headed by the former U.P. President, Dr. Vidal Tan, a group of enterprising professors and employees got together and drew Articles of Incorporation. By January 10, 1947, the U.P. Cooperative was duly registered with the Securities and Exchange Commission (SEC). In 1949 at its new site in Diliman, Quezon City, the cooperative was given a chance to expand its merchandising operations. It was believed that a supermarket conveniently located, operation on a self-service basis and performing home delivery service, would appeal to the population of professionals and students. However, for one reason or the other, the plan was not easily carried out. On January 6, 1966, the cooperative main building was gutted by a big fire that reduced almost all assets into ashes. Some people thought that it was the end of the cooperative operations. But due to courage and dedication of the cooperative management and its members, financial resources were once again pooled together to construct a new building. The cooperative remained solved and was able to provide all the necessary equipment and facilities for the efficient delivery of services to the members. Today, the U.P. Consumers' Cooperative, Incorporated has 3,539 members with total assets of P 8,532,067.47. It also owns two buildings in the University campus located at J.P. Laurel St. and at Area 17, both equipped with modern facilities and appreciable amount of inventory to meet the needs of its members and the community. The administration and management of the UP Consumers' Cooperative, Incorporated is vested to a Board of Directors composed of nine members, who are elected by stockholders during their annual meeting, each serving a term of two-years. Meetings of the Board of Directors are held once a month, where policies are enacted and later implemented by a Manager, duly appointed by the Board. The Cooperative Manager is supported by fifty-six employees servicing the groceries, canteen and two-branch stores, and the administrative support needed in the day- to-day operations. The Organizational Set-up of the U.P. Consumers' Cooperative, Incorporated is shown on the next page. *Arts & Science: store located along the AS walk. *Canteen: located beside the Coop supermarket. *Admin: office located above the Coop supermarket. *Area 2: otherwise known as the Coop supermarket, located beside the Shopping Center. *Area 17: store located near Krus na Ligas. *Purchasing: located in the Admin office